‘They Are Not A Very Good Social Element Even In The Workhouse’: The Vice-Regal Commission On Poor Law Reform In Ireland (1906) And The Workhouse Mother - Bolger, Judy (Socialinė teorija, empirija, politika ir praktika, 2025)
This article examines the representation of mothers, particularly unmarried mothers, within the Irish workhouse system during the nineteenth century as framed by the poor law reform efforts of the Vice-Regal Commission (1906). Established under the Irish Poor Law (1838), the workhouse was designed as a site of relief for the destitute, but proved ill-suited to the needs of women and children, whose presence conflicted with the law’s principles. The Commission’s report is analysed to show how official discourse shaped societal perceptions of poverty and motherhood, despite little legislative change resulting from the report. Class and gender biases are explored through the role of women guardians within the workhouse system. The analysis of the Commission’s findings reveals the deep-rooted social stigmas that marginalised unmarried mothers faced under the Irish Poor Law at the turn of the twentieth century. Ultimately, this article highlights the disparities between those administering relief and those reliant on it, exposing the limitations of poor law reform in addressing women’s lived experiences.